Modeling entrepreneurial intentions among vocational high school students: The roles of education, family, and school support - Rosniawati, Devi; Yunizar, Yunizar (Journal of Educational Management and Instruction (JEMIN), 2025)
This study explores the determinants of entrepreneurial intentions among vocational high school students, emphasizing the roles of entrepreneurial education, family support, and school support, with entrepreneurial self-efficacy as a mediating variable. Using a quantitative research approach, data were collected from 214 students enrolled in the Business and Marketing Department of a vocational high school in Indonesia. The results show that school support has a significant direct influence on entrepreneurial intentions, while entrepreneurial self-efficacy serves as a crucial mediator between external support systems and students’ entrepreneurial aspirations. Notably, although school support exerts the strongest direct effect, its mediated effect through self-efficacy is comparatively smaller. These findings highlight the importance of developing robust educational frameworks, enhancing family encouragement, and strengthening institutional support to cultivate entrepreneurial mindsets among vocational students. The findings of this study have several practical implications, including the need for curriculum development, targeted teacher training in entrepreneurship education, and fostering collaboration between families and schools. This study contributes to the existing literature by proposing a comprehensive model of entrepreneurial intention formation within vocational education, particularly relevant to emerging economies.